Child internalizing symptoms during the COVID-19 pandemic among maltreating and non-maltreating families: Examining the effects of family resources and the Reminiscing and Emotion Training intervention. (August 2022) - Behrens, Brigid; Edler, Katherine; Cote, Kreila; Valentino, Kristin
Abstract: Background: The effects of the COVID-19 pandemic on child functioning have been especially pronounced among low-income families. Protective factors, including sensitive reminiscing and sufficient family resources, may reduce the negative effects of the pandemic on child adjustment. Objective: The current study investigated how family resources during the pandemic, race, maltreatment, and pre-pandemic involvement in an emotion socialization intervention ( M years ago   =  4.37, SD  = 1.36) were associated with child internalizing symptoms during the pandemic. Participants and setting: The study utilized longitudinal data following 137 maltreating and low-income nonmaltreating mother–child dyads ( M age  = 9.08, SD  = 1.88; 54.7% Male). Methods: Mother–child dyads engaged in a randomized controlled trial of the Reminiscing and Emotion Training (RET; Valentino et al., 2019) intervention prior to the pandemic. Dyads discussed shared, past emotional experiences, and during the pandemic, mothers reported on their family resources and their child's internalizing symptoms. A path analysis examined the effects of family resources, race, maltreatment, and the RET intervention on child internalizing symptoms. Results: Family resources during the pandemic were significantly and inversely associated with child internalizing symptoms, b  = −0.07, SE  = 0.02, p  < .01. There was a significant indirect effect of RET on child internalizing symptoms through sensitive reminiscing and a prior assessment of child maladjustment (95% CI [−0.294, −0.001]). Conclusions: These findings suggest adequate family resources and sensitive maternal emotion socialization may be protective against child internalizing symptoms during the pandemic.